Projeto BEPS da OCDE e medidas de combate ao planejamento tributário agressivo na economia digital - Brisola, Anna Karla da Silva (2023)
Globalization allowed companies to become multinationals, at the same time that technology enabled volatility and wide use of intangible assets, inaugurating a new model of economy, with virtual operations, free services that generate new products, users and technical service professionals in several countries. However, this new context facilitated the allocation of resources in favored tax zones and the use of legislative gaps between States to achieve a lower or no tax burden, which is called aggressive tax planning. Another difficulty refers to the connecting elements, that is, the link between countries for income taxation, so that, whether through residence, source, nationality or permanent establishment, these data remained eroded before the characteristics of these business models. Thus, the States, seeking to attract investment and capital for the development of their nation, began to grant income tax reductions, exemptions and deductions to these companies. Other countries, on the other hand, began to institute the digital service tax unilaterally, which generated tax competition between States. In this scenario, with a view to combating these harmful practices and reaching global consensus, the Organization for Economic Co-operation and Development (OECD) created the BEPS Project (Base Erosion and Profit Shiting), later evolving to the BEPS 2.0 Project with a Two Pillar solution. Pillar One sought to establish a link with the market countries where income is generated. Pillar Two foresaw the possibility of a minimum global tax. Hence the relevance of this study, once, as it is a relatively recent measure, the BEPS Project entails a more accurate analysis, preferably relating it to other measures that go against aggressive tax planning in the context of the digital economy. The theme chosen, therefore, is a global concern to restrain tax evasion and achieve tax justice. In this way, the following question arises: in addition to the minimum global tax, what other measures can the Brazilian State use to combat aggressive tax planning in the digital economy? It starts from the hypothesis that the Brazilian State is interested in participating in the international scenario of the fight against aggressive tax planning as defined by the OECD, with the intention of becoming a member of this organization. Added to this, there is the idea that the BEPS 2.0 Project, combined with other protective measures, tends to promote benefits both for multinationals and for the Brazilian nation. In order to answer the proposed question, the general objective is: to study the measures to combat aggressive tax planning that can be adopted by the Brazilian State. With regard to the specific objectives, the following ones can be listed: I. discuss the emergence and consequences of the digital economy in Brazil; II. describe the aggressive tax planning of the Apple case; III. analyze the connecting principles and elements of international corporate income taxation and the current trend of the global economy through the OECD BEPS Project; and IV. explain tax justice and possible countermeasures against aggressive tax planning practices. To achieve these objectives, a qualitative approach was adopted, also using descriptive and exploratory methods and the bibliographic technique of data collection. As main theoretical references, the studies of Caliendo (2009), Schoueri (2005, 2011, 2019, 2020a, 2020b) and Xavier (2010, 2015) were used. The study points to the need to repeal obsolete tax norms and subsequent legislative supply, as well as a typological interpretation of the Constitution for the minimum global tax; finally, for cooperation and tax arbitration as effective and quick alternatives in conflict resolution involving digital companies. Furthermore, as for the minimum global tax, it can be said that it will reduce harmful tax competition and ensure worldwide uniformity in income taxation.